Analisis hasil belajar dalam penggunaan lembar kerja peserta didik (LKPD) Interaktif dengan Aplikasi Wizer.Me Materi Interaksi Sosial - Sulastri, Iis; Mahardika, Nurlaela; Sugiarti, Putri; Sudrajat, Yayan (SINAU : Jurnal Ilmiah Pendidikan Dan Pembelajaran, 2023)
The purpose of this article is to analyze the use of Interactive Student Worksheets using the wizer.me platform on Social Interaction material. The data collection in this study resulted in 43rd students being the sample in the study. They were given learning by using the Interactive Student Worksheet with the wizer.me application and at the end of the lesson they were given a test. In addition, to students who completed this material was 33 of the 43 students who were used as respondents. As well as the effectiveness of using the Interactive Student worksheets with the wizer.me application, it has a completeness percentage of 76.74% so that completeness is in good criteria.